2021
DOI: 10.1186/s40462-020-00237-3
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of realized satellite tracking duration in marine turtles

Abstract: Background Satellite tags have revolutionized our understanding of marine animal movements. However, tags may stop transmitting for many reasons and little research has rigorously examined tag failure. Using a long-term, large-scale, multi-species dataset, we evaluated factors influencing tracking duration of satellite tags to inform study design for future tracking studies. Methods We leveraged data on battery status transmitted with location data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 53 publications
1
30
1
Order By: Relevance
“…Diagnostic data provided strong evidence that battery exhaustion was the main reason why tags stopped relaying data in our study, echoing findings reported by some others (e.g., Hanson et al, 2013;Hofman et al, 2019). In contrast, Hart et al (2021) concluded that damage to their satellite tags was the main reason why data relay stopped. Based on the drop in tag battery voltage, Hart et al (2021) concluded that only 4.1% of their satellite tags attached to turtles stopped relaying data due to battery failure.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Diagnostic data provided strong evidence that battery exhaustion was the main reason why tags stopped relaying data in our study, echoing findings reported by some others (e.g., Hanson et al, 2013;Hofman et al, 2019). In contrast, Hart et al (2021) concluded that damage to their satellite tags was the main reason why data relay stopped. Based on the drop in tag battery voltage, Hart et al (2021) concluded that only 4.1% of their satellite tags attached to turtles stopped relaying data due to battery failure.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, Hart et al (2021) concluded that damage to their satellite tags was the main reason why data relay stopped. Based on the drop in tag battery voltage, Hart et al (2021) concluded that only 4.1% of their satellite tags attached to turtles stopped relaying data due to battery failure. However, since the batteries fail quickly, often direct information on the drop in battery voltage is not received via Argos, as we showed here, with the detection of the battery voltage drop being more frequent when more battery status diagnostic information was received.…”
Section: Discussionmentioning
confidence: 99%
“…For two other individuals, biofouling was not indicative of tag failure, but the decrease in swimming speed might suggest that the turtles could have died due to cold-stunning in winter. The rapid growth of immature loggerhead turtles could also explain a premature tag detachment (Hays et al, 2021), leading to a shorter tag life (mean: 145 ± 152 days, range: 18-679 days) compared to other studies based on adult individuals, e.g., loggerheads retain 50% of their tags for 584 days (Hart et al, 2021). For future deployments, we recommend a careful battery management based on a severe duty cycling to extend tag life in immature individuals (Christiansen et al, 2016).…”
Section: Resident Behavior In European Coastal Watersmentioning
confidence: 97%
“…The algorithm accounted for the Argos quality to predict the daily locations using Argos error ellipses for the tags deployed after 2011, while the location classes (0, 1, 2, 3, A or B) were used for the remaining tags. Following Hays et al (2021) and Hart et al (2021), assessment of tag failure was conducted on the data available using the three following metrics: battery voltage, wet/dry switches and the number of Argos transmissions.…”
Section: Movement Analysismentioning
confidence: 99%
“…We fitted platform terminal transmitters (PTTs; SPOT5, SPOT6, or SPLASH10; Wildlife Computers, Redmond, WA) to loggerhead females after they nested (n = 110 turtles), according to established protocols (NMFS-SEFSC, 2008) and methods outlined in Hart et al (2014Hart et al ( , 2018bHart et al ( , 2021; methods were approved by Institutional Animal Care and Use Committee Protocol (see Acknowledgments for more details). All tagged turtles were released within 2 hr at their capture location.…”
Section: Satellite Tracking and Switching State-space Modelingmentioning
confidence: 99%